Aplikasi dan Pengujian Keakurasian Nilai Hasil Dengan Metode t-Test Untuk Perhitungan Zakat Mal Berbasis Android - Ahmad Fauzi (Universitas Bina Sarana Informatika, 2018)
Technology invented by man in order to facilitate the process of which is considered difficult, all have to understand all sorts of fields of science respective expertise to be right in getting a value, as in the calculation of a charity mall where there is a science that involves a variable and there terms and kententuannya, not all people understand and understand the calculation of zakat mal whereas in Islamic law is obligatory upon a Muslim issue a zakat mal reference to a letter (At-Taubah: 34-35), but there is also for Muslims who are not obliged to issue a zakat mal on the problems it can be concluded that in paying zakat there are required and some are not required, computing applications zakat mal this is an application that functions as a calculator or media calculating zakat mal and give information whether a Muslim is obliged to pay or not obligated to pay however, this application will also be tested accuracy value by doing manual calculation so as to set a value for the accuracy of this comparison.